Studi Perbandingan Kualitas Udara di Kota Indonesia Terdampak Infeksi Saluran Pernapasan Akut - Muhammad Thoifur Fajar (Yayasan Literasi Sains Indonesia, 2024)
Air quality affects the activities carried out by humans. Healthy air quality will support human activities. On the other hand, unhealthy air quality will disrupt human activities by causing respiratory tract diseases. The aim of the research carried out was a comparative study of the air quality of Indonesian cities based on cases of acute respiratory infections. The research method is descriptive analysis of the air quality index (AQI) and air particles (PM) in the city of Palembang, the city of Cileungsir, the city of Serang, the city of Jambi, the city of South Tangerang, the city of Bandung, the city of Jakarta, the city of Pekanbaru, the city of Denpasar and the city of Semarang on effective work, weekends and morning, afternoon, evening and night time periods. The results of the research show that the air quality is quite good in the cities of Denpasar and the city of Semarang and the city with high pollution is the city of Palembang. This research provides information and awareness in maintaining air quality so that it can maintain and strive for healthy air quality so that it supports human activities and does not cause respiratory infections